MEMPREDIKSI JUMLAH PRODUKSI KEDAI KOPI KAGANANGAN MENGGUNAKAN METODE FUZZY TSUKAMOTO - Herlina Kristin Rahel; Hana Silviana Sutanto; Imelda Susilawaty; Minarni (JURNAL ILMIAH BETRIK, 2023)
Kaganangan Coffee Shop is a trading business whose business line is a shop. Because the high level of competition makes more and more similar businesses pop up, Kedai Kopi Kaganangan is required to design a strategy that can provide more value to consumers at a more affordable cost. The habit of drinking coffee among Indonesian people has become a lifestyle in society. From the past until now, this coffee business continues to be enjoyed by teenagers to parents. One of the coffees that have been popular with coffee lovers in the city of Sampit is the Kaganangan Coffee Shop. This coffee is often visited by coffee lovers when teenagers come home from school and adults during recess or go home from the office which is located on H.M Arsyad Street, Sampit. One of these coffee shops makes it difficult for business owners to determine how much coffee production they must have to meet sales demand. To predict coffee production for one week, the data used may include, coffee sales data during the previous period can be used to predict coffee demand in the coming week. This data can be obtained from in-store sales records or consumer surveys, current coffee inventory data can be used to predict how much coffee to produce in the coming week. These data can be combined and analyzed using the Tsukamoto fuzzy method, to make predictions of coffee production for one week. In addition, external factors such as weather, raw material prices, and market conditions also need to be considered in making predictions. The purpose of this research is to overcome the problem with the Tsukamoto fuzzy method used by the author, and the results obtained are said to produce 821 Kaganangan Coffee. Therefore, the results of this study can be used as a consideration in determining the average production amount of Kaganangan Coffee.